Hormona de crecimiento en sujetos varones de diferentes altitudes - Mujica, Elydia (2010)
Objectives: To determine growth hormone (GH) serum levels in adult males at sea level (Lima, 150 msnm) and high altitude (Cajamarca: 2 750 msnm, Huancayo: 3 280 msnm, Morococha: 4 540 msnm). Design: Descriptive, observational, transversal and prospective study. Location: Lima, Cajamarca, Huancayo y Morococha, Peru. Participants: Male adult natives of different altitude settings. Interventions: With informed consent blood samples were obtained from the forearm in fasting and resting conditions from 41 young adult male subjects 20 to 35 years old [12 subjects at sea level (Lima 150 m), 10 subjects in Cajamarca (2 750 m), 12 subjects in Huancayo (3 280 m), and 7 subjects in Morococha (4 540 m)]. Main outcome measures: Serum growth hormone (GH) levels. Results: GH mean values found were at 4 540 m: 3,87 ± 0,16 ng/mL; at 3 280 m: 1,31 ± 0,09 ng/mL; at 2 750 m: 0,63 ± 0,08 ng/mL; and at 150 m: 0,54 ± 0,04 ng/mL. There was significant difference (p <0,05) between values found at altitudes 4 540 m and 3 280 m above sea level (150 m). No significant difference was found between values found at 2 750 m and 150 m. Conclusions: Adult male growth hormone serum levels were higher at Huancayo (3 280 msnm, n=12) and Morococha (4 540 msnm, n=7) than at sea level (Lima 150 msnm, n=12).